The Methyl-CpG-Binding Protein Mbd2 Regulates Susceptibility to Experimental Colitis via Control of CD11c+ Cells and Colonic Epithelium - Jones, Gareth-Rhys; Brown, Sheila L.; Phythian-Adams, Alexander T.; Ivens, Alasdair C.; Cook, Peter C.; MacDonald, Andrew S. (Frontiers in Immunology, 2020)
Methyl-CpG-binding domain-2 (Mbd2) acts as an epigenetic regulator of gene expression, by linking DNA methylation to repressive chromatin structure. Although Mbd2 is widely expressed in gastrointestinal immune cells and is implicated in regulating intestinal cancer, anti-helminth responses and response to colonic inflammation, the Mbd2-expressing cell types that control these responses are incompletely defined. Indeed, epigenetic control of gene expression in cells that regulate intestinal immunity is generally poorly understood, even though such mechanisms may explain the inability of standard genetic approaches to pinpoint the causes of conditions like inflammatory bowel disease. In this study we demonstrate a vital role for Mbd2 in regulating murine colonic inflammation. Mbd2-/- mice displayed dramatically worse pathology than wild type controls during dextran sulphate sodium (DSS) induced colitis, with increased inflammatory (IL-1β+) monocytes. Profiling of mRNA from innate immune and epithelial cell (EC) populations suggested that Mbd2 suppresses inflammation and pathology via control of innate-epithelial cell crosstalk and T cell recruitment. Consequently, restriction of Mbd2 deficiency to CD11c+ dendritic cells and macrophages, or to ECs, resulted in increased DSS colitis severity. Our identification of this dual role for Mbd2 in regulating the inflammatory capacity of both CD11c+ cells and ECs highlights how epigenetic control mechanisms may limit intestinal inflammatory responses.